Fairy - Bouchard, Dave.; Griffiths, Dean, 1967- (Victoria, BC ; Custer, WA : Orca Book Publishers, 2001)
The Harley-riding fairy who takes care of the magical needs of the neighborhood steps in when Victoria Stubbs loses her first tooth and her nonbelieving father wants nothing to do with the tooth fairy.
Keywords: Teeth -- Fiction; Fairies -- Fiction